Lepanthes elusiva – a New Species of Lepanthes (Orchidaceae: Pleurothallidinae) from Tapantí Area in Cartago, Costa Rica and a Glance to Other Species of the Genus in a Small Area Around the Río Grande de Orosi in Costa Rica - Bogarín Chaves, Diego Gerardo (2019)
With about more than 120 species, Lepanthes is one of the most species-rich orchid groups represented in Costa Rica. Here, we describe and illustrate a new species from the Tapantí National Park, a megadiverse area in the Cordillera de Talamanca from where several new species of Lepanthes have been described. Lepanthes elusiva resembles Lths. regularis, however, it differs in the denticulate sepals, the ovate, subfalcate lobes of petals, and the lower lobes of the lip which are superimposed. The lip of Lepanthes elusiva resembles the lip of Lths. elvirae with its broad laminae extending far from the column apex, however, it differs from that species mainly by the ovate to elliptic leaves and the oblong lobes of petals. We provide additional information on the new species such as ecology, etymology, distribution map, phenology and detailed morphological drawings and scanning electron microscope micrographs as well as photographs of the species of Lepanthes from the area of Tapantí.